African elephant genetics: request for samples - Roca, Alfred; Georgiadis, Nicholas; O'Brien, Stephen (Pachyderm, 2002)
Reviews ongoing research focused in a continent-wide genetic survey of African elephant conducted under the aegis of the Laboratory of Genomic Diversity in Maryland, USA and Mpala Research Centre in Nanyuki, Kenya. References published data, notes the geographic locations from which samples have orginated thus far, and the areas from which representative data is lacking. Requests additional samples and outlines the format under which samples of tissue (including muscle, organs and skin), blood and dung should be taken and where to send them.